PSALM 62: PRAYER, ACCUSATION, DECLARATION OF INNOCENCE, SELF-MOTIVATION, SERMON, OR ALL OF THESE? - P J Botha (Acta Theologica)
Because of its seeming mix of different styles, Psalm 62 has intrigued researchers for a long time. It has been regarded by many as the prayer of an innocent person who was accused of some wrongdoing, but the direct exhortation to the “people” of God to put their trust in him seems to argue against this. The pertinent influence of wisdom-thinking also agitates against a reconstructed cultic setting. Some investigators have consequently argued that the psalm is a conflation from different sources. This article attempts to contribute to the debate about the seeming mix of styles by arguing from a social-scientific analysis that the psalm should be read against the background of a post-exilic context of exploitation in Jerusalem and the ensuing debate about the value of continued dedication to God.